The Effect of Knowledge Management on Investor Behaviour - Mochammad Nugraha Reza Pradana; Afrianti Elsye Vanomy (Almana : Jurnal Manajemen dan Bisnis, 2020)
Market efficiency will be achieved if investors can think rationally. Therefore, knowledge management is needed to create rational investor behaviour in the Indonesian Capital Market. This study aims to analyze the role of knowledge management on investor behaviour. This type of research is quantitative research. The population of this study is 211 investors who are registered at the Investment Gallery Universal University. The sample in this study amounted to 55 investors with the random sampling technique. The data analysis technique used is the Structural Equation Model (SEM) with SmartPLS version 3.0. The results showed that Knowledge Management has a significant influence on Investor Behaviour.